Selected modifiable lifestyle areas influencing diseases of the digestive - Ślósarz, Dominika; Kempiński, Radosław; Jakubowska, Luba (Journal of Education Culture and Society, 2021)
Thesis. The multifactor aetiology of the diseases of the digestive system is frequently connected with lifestyle, including diet, exposure to stress, and alcohol consumption. These factors are part of the modifiable factors influencing state of health, and the presentation of their influence on the pathogenesis of the diseases of the digestive system may lead to increased social awareness, improved health, and decreased healthcare expenditures. Concept. The article is a review, presenting the results of latest research on the influence of selected behavioural factors (health behaviours) in the functioning of the digestive system. Results and conclusion. In order to prevent diseases of the digestive system Mediterranean diet, reduction of alcohol consumption, and looking after emotional wellbeing and physical fitness are recommended. The understanding of health as looking after and enrichment of resources, rather than a lack of illness, is connected with patients’ responsibility for their own health. Frequently, it is only with the diagnosis of an illness that patients decide to change their behaviour. Meanwhile, healthy lifestyle ought also to be understood as one of the most significant elements of the prevention of diseases of the digestive system. Such understanding is part of the paradigm of behavioural gastroenterology(Jia, Jiang, & Liu, 2017), whose representatives emphasise that it is important for healthy lifestyle and psychological factors to be taken into account in treatment as well as diagnosis, rehabilitation, and prophylactics of the diseases of the digestive system.